Antibiotic Prescribing Variability in a Large Urgent Care Network: A New Target for Outpatient Stewardship. (23rd October 2019) - Stenehjem, Edward; Wallin, Anthony; Fleming-Dutra, Katherine E; Buckel, Whitney R; Stanfield, Valoree; Brunisholz, Kimberly D; Sorensen, Jeff; Samore, Matthew H; Srivastava, Raj; Hicks, Lauri A; Hersh, Adam L
Abstract: Improving antibiotic prescribing in outpatient settings is a public health priority. In the United States, urgent care (UC) encounters are increasing and have high rates of inappropriate antibiotic prescribing. Our objective was to characterize antibiotic prescribing practices during UC encounters, with a focus on respiratory tract conditions. This was a retrospective cohort study of UC encounters in the Intermountain Healthcare network. Among 1.16 million UC encounters, antibiotics were prescribed during 34% of UC encounters and respiratory conditions accounted for 61% of all antibiotics prescribed. Of respiratory encounters, 50% resulted in antibiotic prescriptions, yet the variability at the level of the provider ranged from 3% to 94%. Similar variability between providers was observed for respiratory conditions where antibiotics were not indicated and in first-line antibiotic selection for sinusitis, otitis media, and pharyngitis. These findings support the importance of developing antibiotic stewardship interventions specifically targeting UC settings. Abstract : We describe antibiotic prescribing in a large network of urgent care (UC) clinics. The high volume of infectious diseases encounters and extreme provider variability in antibiotic prescribing frequency and quality highlight the importance of antibiotic stewardship interventions specifically targeting UCs.